Upaya Pencegahan Kekerasan Terhadap Anak dan Perempuan dalam Menciptakan Lingkungan Ramah Keluarga - Purnamasari, Sulfi; Kusworo, Kusworo; Rahayu, Purwati Yuni (Jurnal Loyalitas Sosial: Journal of Community Service in Humanities and Social Sciences, 2019)
Violence against children and women is a common phenomenon in the midst of people's lives. In the city of Depok in the period of 2018. From existing data, there are still 101 cases of child abuse and 78 cases of adult violence. The purpose of community devotion in RW 05 of the District of Sukmajaya Depok is to give understanding to the community about the causes of various problems related to Actions that contradict the laws that occur in the home, both concerning action on children and women and efforts that can be pursued as preventive measures to avoid them. The activities of devotion are conducted using the method of counseling. By looking at the phenomenon that occurs in the environment RW 05. From the analysis of the results that there are still several incidents that lead to indications of the absence of human treatment in both children and women in the neighborhood of RW 05, in addition to the lack of citizen understanding RW 05 on violence To children and women and their prevention efforts. Following this, for some time, there is a need for evaluation on the results of the extension that has been done whether to give significant results on behavioral change and understanding of citizens RW 05 related to the problem. From the evaluation results can be determined steps that can be taken next.